Phytochemical study of the alkaloids from the bulbs of Eucharis grandiflora Planchon (Fam. Amaryllidaceae) - Garcia, Ma. Victoria G.; Santos, Rizalina B.; Concepcion. Adoracion B. (Quezon City: Department of Pharmaceutical Chemistry, College of Pharmacy, University of the Philippines, 1983.)
The study covers the extraction of the alkaloid from the bulbs of Eucharis grandiflora Planchon (Fam. Amaryllidaceae) using a polar solvent, ethanol. A phytochemical study was made on the concentrated ethanol extract by thin layer chromatography and determination of melting point of the isolated crystals from the preparative chromatography.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, October 1983.
Keywords: Alkaloids; Plants -- Analysis; Amazon Lily